2017
DOI: 10.1097/mbc.0000000000000543
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficiency under current use of human fibrinogen concentrate in trauma patients with life-threatening hemorrhagic disorders

Abstract: The aim of the study was to assess the influence of fibrinogen concentrate on survival when it is used in trauma patients with life-threatening hemorrhagic disorders. Secondly, to evaluate when the fibrinogen concentrate administration maximizes its efficacy, and to describe what other concomitant treatment the patients received in order to control their life-threatening hemorrhage. Retrospective, observational, and multicenter study was carried out in three trauma areas between June 2012 and June 2014. The to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Moreover, the use of activated oral charcoal (within 2 hr) in patients who recently ingested DOACs is recommended by some authors . For cases in which supportive care and drug discontinuation are not sufficient, if immediate reversal is required and the patient is having life‐threatening bleeding, nonspecific procoagulant or antifibrinolytic agents can be added to PCCs, such as fresh‐frozen plasma (FFP), fibrinogen concentrate or cryoprecipitate, and tranexamic acid . Hemodialysis for dabigatran removal may also be used.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of activated oral charcoal (within 2 hr) in patients who recently ingested DOACs is recommended by some authors . For cases in which supportive care and drug discontinuation are not sufficient, if immediate reversal is required and the patient is having life‐threatening bleeding, nonspecific procoagulant or antifibrinolytic agents can be added to PCCs, such as fresh‐frozen plasma (FFP), fibrinogen concentrate or cryoprecipitate, and tranexamic acid . Hemodialysis for dabigatran removal may also be used.…”
Section: Discussionmentioning
confidence: 99%
“…45 The results of Gonzalez-Guerrero et al support the possibility that raising patients' plasma fibrinogen levels may, potentially, decrease mortality rates. 42 Moreover, the results of studies comparing guided treatment with coagulation factor concentrates (principally FC) versus treatment based on FFP have reported reduced transfusion and lower rates of MOF with coagulation factor concentrates. 16,18 The study by Innerhofer et al was stopped early for futility and safety reasons, with a much increased need for rescue therapy in patients receiving FFP rather than coagulation factor concentrates (odds ratio [OR]: 25.34).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of nonguided treatment with allogeneic blood products did not employ a ratio-based approach. 12,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] These studies varied in outcomes and treatment approach, with mortality and ISS varying widely (ISS: 16.8-42.5). The highest mortality rates were observed in critically ill patients receiving ultramassive (defined as transfusion of 20 U RBC over the course of any 2 consecutive calendar days) or massive transfusions (mortality rates of 63% at 30 days and 58.5% while in hospital, respectively), 27,41 patients with coagulopathies (30day mortality: 50%), 32 and patients with a greater degrees of hemodynamic instability (group with highest Shock Index stratification had mortality rate of 39.8%).…”
Section: Studies Utilizing Nonguided Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Several retrospective studies and case series have reported improved outcomes using FC in trauma [62,87]. There have been some debates about its clinical benefits [88,89] and its use as a universal hemostatic agent [90].…”
Section: Fibrinogen Concentratementioning
confidence: 99%